Avaliação da resistência de união de diferentes sistemas de cimentação adesiva ao esmalte e a dentina - Mutti, Isabele do Nascimento (2010)
Objective: The aim of this study was to evaluate the bond strength to enamel and dentin of a self-adhesive resin cement applied with different cementation strategies, using a conventional resin cement as control. Material and Methods: Sixty healthy human molars were selected and allocated into 6 groups (n=10) according to cementation system and dental substrate: ARCe (Adper Single Bond 2 + RelyX ARC in enamel), U100e (RelyX U100 in enamel), a+U100e (Phosphoric acid + RelyX U100 in enamel), ARCd (Adper Single Bond 2 + RelyX ARC in dentin), U100d (RelyX U100 in dentin), a+U100d (Phosphoric acid + RelyX U100 in dentin). Composite resin blocs (Filtek Z250) were confectioned with dimensions of 4mm x 6mm x 4mm to enamel and 7mm x 7mm x 4mm to dentin, and immediately cemented on the surfaces according to each group. Each resin-tooth assembly was stored in 370C distilled water for 24 hours and longitudinally sectioned into two axis producing specimens (sps) with area of approximately 1mm2. The sps were submitted to microtensile test at 1 mm/min and failures were observed with stereomicroscopic magnifying glass with 32x magnification. Data were submitted to Analysis of Variance and Tukey s test (5%). Results: Means (MPa) were: ARCe: 50.5; U100e: 24.5; a+U100e: 53.5; ARCd: 36.0; U100d: 26.7; a+U100d: 25.9. No statistical difference was found between groups that used acid etching in enamel, thus presenting values higher than U100 without previous acid etching. In dentin, values were higher (p<0.05) for ARCd compared to U100d and a+U100d groups, which presented similar results. Conclusions: Previous acid etching prior to cementation in enamel enhanced bonding of self-adhesive cement to dental structure.In dentin this acid etching did not influenced bond strength values of this cement.